Ukuran Pemusatan dan Penyebaran Data - Rifki, Aulia; Rahimah, Siti; Arianto, Arianto; Zulpan, Zulpan (Indo Publishing, 2026)
Statistics is the science of collecting, processing, presenting, and analyzing data in order to provide meaningful information for decision-making. One of the fundamental concepts in statistics is the measure of central tendency and data dispersion. Measures of central tendency, which include mean, median, and mode, describe the central value of a data set. Meanwhile, measures of dispersion, such as range, variance, and standard deviation, are used to determine how far the data values deviate from the center. This article aims to provide a comprehensive understanding of the concepts, formulas, and applications of measures of central tendency and dispersion in the context of learning statistics. With a proper understanding, students are expected to analyze data more critically, recognize variation within a phenomenon, and connect the analysis results to real-life problems. The discussion in this paper is expected to strengthen students’ analytical skills and provide a solid foundation for studying more advanced statistical methods